Peranan Petugas Imigrasi Terhadap Pengungsi Di Indonesia Terkait Dengan Berlakunya Undang-Undang Nomor 6 Tahun 2011 - Rajagukguk, Eko Yudis Parlin; Suhaidi, Suhaidi; Leviza, Jelly; Lubis, Anggreni Atmei (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
Nowadays, the refugees’ problems have become a concern towards international society. The study aims to discover how the role ofimmigration officers to organize the foreigners may enter Indonesian territory. Then, the research discover how the impact of refugees existence towards Indonesian people. Then again, what is barrier faced by the immigration officers in handling the refugees in Immigration Detention House in Medan. The method of approach used in this study is a normative approach based on the laws and regulations as a review at the conceptual level about the meaning and purpose of various national legal regulations Number 6 of 2011 concerning Immigration against refugees in Indonesian territory. Data Collection Tools, Library Research (data analysis) Analysis of the data in this study using qualitative methods. The process of analyzing data in qualitative research begins by examining all data collected from various sources, namely from interviews, observations that have been written in field notes, personal documents, official documents, pictures, photographs and so on. The immigration officers of Indonesia manage the foreigners that entering Indonesian territory by applying selective policy. The refugees in Indonesian territory have a crucial impact towards Indonesian society.